Implementasi kecerdasan buatan untuk personalisasi kurikulum adaptif dalam era society 5.0. - rohmaniah, izzatur (Maliki Interdisciplinary Journal, 2026)
This study investigates how Artificial Intelligence (AI) can be leveraged to foster innovative, inclusive, and adaptive learning experiences within the context of Society 5.0. The authors contend that AI is a pivotal factor driving the modernization of education, particularly through its capacity to personalize content, enhance feedback responsiveness, and streamline administrative workloads.The methodology employed is a qualitative review, utilizing literature analysis and examination of practical case studies, including the implementation of AI-driven adaptive learning, educational chatbots, and Virtual Reality applications. Key findings reveal a dual benefit of AI: a reduction in non-teaching duties for educators and the ability to deliver individually tailored learning programs, alongside an improvement in students’ digital literacy. However, this integration faces hurdles, such as resistance to change and unequal access to technology. Moving forward, the researchers underscore the necessity of comprehensive policies and targeted training for teachers to ensure AI implementation is ethical and effective, aligning with the human-centric goals of Society 5.0.